The fragility of language and the encounter with God : on the contingency and legitimacy of doctrine - Klug, Florian, 1987- (Fortress Press, 2021)
The Fragility of Language and the Encounter with God offers a theological account of the contingency of language and perception and of how acknowledging that contingency transforms the question of the development of doctrine. Klug argues that statements of faith cannot overcome contingency. Instead, the Catholic notion of receptive tradition is an attempt to cope rationally with the fragility of perception and language in humanity's orientation toward God.